(untitled) (Bangladesh Medical Journal, 2024)
There is a need to have a formal health program for the medical students, set guidelines for students to follow if they fall ill and provision of rational medication. Students need to be made aware of the dangers of self-treatment and investigation. This cross-sectional study was conducted among the undergraduate medical students of US Bangla Medical College (USBMC), Narayangonj from July to December 2022. The study aims to assess the health seeking behavior and self-medication among the students. Data were collected by interviewing students using a pre-designed questionnaire and twenty Likert items were prepared for data collection. Data were analyzed by using SPSS (Statistical Package for the Social Sciences) version 25. Total 293 students were interviewed, among them male - female ratio was 1.23:1 and the age range of the participants was 17 to 28 years. Most of the (70%) students were belonged to upper-middle class family; where 21% from upper class, 8% from lower middle class, and only 1% from the working class family. Regarding the father’s educational status of the students more than two-third (69%) of their fathers completed university degree, 29% completed higher secondary or secondary level of education and few (2%) had informal education. Most of the students (81%) used to take medicine without prescription/ self medication. Among the students around one-fourth of them used to take both paracetamol (26%) and painkiller (24%) as self-medication; where 13% of the students used to take antibiotic. Regarding the opinion of the well established definition of ‘Health’ that is “Health includes physical, mental and social well-being and not just absence of disease/ infirmity” most of the students (90%) gave positive statement (agree 58% and strongly agree 32%); where 5% of them were neutral and rest 5% were disagreed. Nearly two-third (65%) of the students expressed their opinion positively (agree 49% and strongly agree 16%) on “seek help immediately when they develop some physical symptoms” that is they seek immediate help for their illness; where 14% of them were neutral and rest 21% were disagreed. More than one-third (35%) of the students stated the reason for self-medication related to their too busy schedule to visit physician and 21% stated that the illness was too minor for consultation; other reasons were knowledge about the drug and illness, follow old prescription, over the counter drugs etc. Almost one-third (30%) of the students opined positively that public health care facilities provide standard health care, but more than one-third (36%) did not comment and rest one-third (34%) differed on it. Remarkably used self-medicated drugs were paracetamol (26%), painkiller (24%), 13% and others NSAIDs/ Analgesics, Antacid/ PPI, Vitamins, antitussive, antihistamines. The statistical test revealed that there is a strong relationship of their opinion on attention to mental physical well-being for healthy lively-hood between coping ability, seek the best care from college hospital and seek help for sensitive matters other than own college hospital (at 5% level of significance). To ensure better health seeking behavior and good practice knowledge of medical students was not absolutely satisfactory. Awareness regarding demerits of self-medication like antibiotics resistance and side effect of drugs would be build among the students. This study would facilitate for increase of medical knowledge and promotion of higher health-seeking behavior. Bangladesh Med J. 2022 Sept; 51(3): 37-42